PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN GUIDED NOTE TAKING - Utami, Nita Putri; Yulia, Yulia; Ramadona, Serli (UIN Imam Bonjol Padang, 2023)
This study aims to develop lesson plans and handouts based on Guided Note Taking on Algebraic Operations material. This type of research is development research with a 4-D model proposed by S. Thiagarajaan (1974) which consists of four stages of development, namely definition, design, development and dissemination. The define stage consists of: a) educator analysis b) student analysis c) concept analysis d) curriculum/syllabus analysis and learning objectives. The design phase consists of: a) device design b) instrument design and validation of learning device assessment instruments. The develop stage consists of: a) validity stage b) practicality stage. The results of this study indicate that based on the assessment of 5 validators, the learning tool, namely the RPP developed, meets the criteria of being very valid with an average of 90% and the Handout meets the criteria of